Women's Autonomy and Maternal Health Care Utilization in a Community of Dang District, Nepal - Sharma, Sharmila; Pradhananga, Renuka Devi; Gautam Bhandari, Saraswoti; Acharya, Ankit (Journal of Karnali Academy of Health Sciences, 2021)
Introduction: Maternal health services utilization during pregnancy, childbirth, and postnatal period is vital for both mother and child. Women’s autonomy is one of the determinants of maternal health care utilization. The objective of the study was to find out women’s autonomy and its effect on maternal health care utilization. Methods: Descriptive cross-sectional study design was carried out among 166 women having a child under one year using simple random sampling via lottery method from ward number 1 and 2 of Ghorahi, Dang, Nepal. Semi-structured interview schedule from 2nd July to 28th July 2017 was used to collect data, which were analyzed using descriptive and inferential statistics. Multivariate logistic regression was used to find association between women’s Autonomy and maternal health care utilization. Results: The study findings revealed that less than half (47%) of women had a higher level of Autonomy. The majority of respondents, 77.7% and 76.5%, had utilized ANC and delivery care services respectively, whereas only one-third (32.5%) had utilized postnatal care adequately. The overall maternal health care utilization was only 25.9%. Women who had a higher autonomy level were two times more probable (OR=2.870, 95% CI: 1.169-7.048) for utilizing maternal health care service than who had lower level of autonomy. Other factors which affected maternal health care utilization were the age of women (OR=4.747, 95%CI: 1.416-15.919) and the educational level of women (OR=3.157, 95% CI: 1.196-8.328). Conclusions: Both autonomy and maternal health care utilization were low. Women’s autonomy was one of the determinants for maternal health service utilization.